Karakteristik Yoghurt Berdasarkan Variasi Penambahan Konsentrasi Pati Jagung - Saman, Widya Rahmawaty; Ahmad, Lisna; Harun , Fahri Rahmawati (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
Corn yoghurt is one of the yoghurt innovations made from corn starch, processed by a method similar to yoghurt making in general. This study used a completely randomised design (CRD) with one variable, namely the concentration of corn starch added. Each treatment was repeated three times and there were three treatments and one control. Yoghurt with 15% corn starch added showed the highest pH value and sweetness level. Total Dissolved Solids (TPT) was also highest in symbiotic yoghurt with 15% corn starch added. Organoleptic assessment which included taste, colour, texture, and aroma showed that yoghurt with the addition of 10% corn starch had the highest values for taste and texture. The colour of yoghurt from each treatment was almost uniform, while for aroma, panelists preferred yoghurt without added corn starch.